Pengaruh Risiko Pembiayaan dan Risiko Likuiditas Terhadap Kinerja Keuangan Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Dahlia; Mery Yani (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study discusses the effect of financing risk and liquidity risk on the financial performance of three Islamic banks listed on the Indonesia Stock Exchange for the period 2015 to 2015. 2019, namely BRI Syariah Bank, Syariah National Pension Savings Bank and Panin Dubai Syariah Bank. Variables in the study. The analysis used is panel data regression analysis. The selection of the best model between the fixed effect method and the common effect method is carried out using the Chow test. If the fixed effect is selected as the best method, then the Hausman test is carried out to choose between the fixed effect method and the random effect method. The test results show a probability value > 0.05, so Ho is accepted. The panel regression estimation model in this study is the Common Effect Model. The results showed that simultaneously the two variables had an effect on banking performance. Partially, the financing risk (NPF) and liquidity risk (FDR) variables had no significant effect on ROA.